Discovery of a novel 2-(1H-pyrazolo[3, 4-b]pyridin-1-yl)thiazole derivative as an EP1 receptor antagonist and in vivo studies in a bone fracture model. Issue 14 (1st August 2018) - Atobe, Masakazu; Naganuma, Kenji; Kawanishi, Masashi; Hayashi, Takahiko; Suzuki, Hiroko; Nishida, Masahiro; Arai, Hirokazu
Graphical abstract: Highlights: The effort to reduce the lipophilicity led to improve the pharmacokinetics profile. PK study of4 showed good exposure for long-term in vivo studies. The possibility of fracture healing has been showed in bone fracture model with4 . Abstract: We describe a medicinal chemistry approach to the discovery of a novel EP1 antagonist exhibiting high potency and good pharmacokinetics. Our starting point is1, an EP1 receptor antagonist that exhibits pharmacological efficacy in cystometry models following intravenous administration. Despite its good potency in vitro, the high lipophilicity of1 is a concern in long-term in vivo studies. Further medicinal chemistry efforts identified4 as an improved lead compound with good in vitro ADME profile applicable to long term in vivo studies. A rat fracture study was conducted with4 for 4 weeks to validate its utility in bone fracture healing. The results suggest that this EP1 receptor antagonist stimulates callus formation and thus4 has potential for enhancing fracture healing.